G protein-coupled estrogen receptor expression in postnatal developing mouse retina - Piñon-Teal, Wendy L.; Ogilvie, Judith Mosinger (Frontiers in Ophthalmology, 2024)
IntroductionEstrogen has emerged as a multifaceted signaling molecule in the retina, playing an important role in neural development and providing neuroprotection in adults. It interacts with two receptor types: classical estrogen receptors (ERs) alpha and beta, and G protein-coupled estrogen receptor (Gper). Gper differs from classical ERs in structure, localization, and signaling. Here we provide the first report of the temporal and spatial properties of Gper transcript and protein expression in the developing and mature mouse retina.MethodsWe applied qRT-PCR to determine Gper transcript expression in wild type mouse retina from P0-P21. Immunohistochemistry and Western blot were used to determine Gper protein expression and localization at the same time points.ResultsGper expression showed a 6-fold increase during postnatal development, peaking at P14. Relative total Gper expression exhibited a significant decrease during retinal development, although variations emerged in the timing of changes among different forms of the protein. Gper immunoreactivity was seen in retinal ganglion cells (RGCs) throughout development and also in somas in the position of horizontal cells at early time points. Immunoreactivity was observed in the cytoplasm and Golgi at all time points, in the nucleus at early time points, and in RGC axons as the retina matured.DiscussionIn conclusion, our study illuminates the spatial and temporal expression patterns of Gper in the developing mouse retina and provides a vital foundation for further investigations into the role of Gper in retinal development and degeneration.